Answer:
4x - 3y + 6z.
Step-by-step explanation:
He wrote 62 instead of 6z on the first line.
He made 2 mistakes on the last line:
He didn't subtract the x terms, there was no term = 5.
The -3y + 6z does not simplify to 3yz, the terms have an add process not a multiply.
The correct solution is
5x - x - 3y + 6z
= 4x - 3y + 6z.
X × .60 = answer
%60X = answer
Answer:
The value of (g*h) (-3) is
Step-by-step explanation:
If
and
We have to find (g*h) (-3)
First multiply g(x) with f(x)
simplify
Now, put x= -3 in above expression
Therefore, the value of (g*h) (-3) is
I think:- every point that expresses the graph of the function f must be subtracted 1
-2,2 is the answer i think